Theology, church, and ministry : a handbook for theological education - Dockery, David S. (Nashville, TN : B & H Academic, 2017)
We live in a precarious time when many are questioning the necessity of formal thelogical education for ministers. Theology, Church and Ministry, helps readers understand the critical role theological education plays in equipping God-called ministers for service in the church. This distinct resource explains both the development and purpose of theological education as well as its role in student formation.
Foreword / Timothy George -- Theological education : an introduction / David S. Dockery -- The foundation and shape of theological education / Mark L. Bailey -- Intellectual discipleship and the value of theological education / Sarah P. Sumner -- Theological education and ministry calling / Michael Duduit -- Theological education and spiritual formation / Dana M. Harris -- Biblical inspiration, authority, and canonicity / D. Jeffrey Bingham -- The languages of the Old Testament / Kenneth A. Mathews -- The study of the language of the New Testament / Constantine R. Campbell -- Introduction to the Old Testament / Eric J. Tully -- Introduction to the New Testament / Ray Van Neste -- Theology of the Old Testament / Daniel I. Block -- Theology of the New Testament / Christopher W. Morgan -- From Bible to theology / Kevin J. Vanhoozer -- Systematic theology / Malcolm B. Yarnell III -- Church history and historical theology / Gregory A. Wills -- Apologetics / R. Alan Streett -- Theological ethics / Graham A. Cole -- Theology, preaching, and pastoral ministry / Robert R. Smith -- Theology, evangelism, and missions / Charles (Chuck) E. Lawless -- Theology, worldview formation, and cultural engagement / Owen Strachan -- Theology for church, worship, and ministry / Daniel L. Akin -- Theology and the global Church / Timothy C. Tennent.
Print version record.
Includes bibliographical references and indexes.
Master record variable field(s) change: 072, 082
Keywords: Clergy -- Training of; Theology -- Study and teaching; Theological seminaries; Clergy -- Training of; Theological seminaries; Theology -- Study and teaching; RELIGION / Christian Theology / Systematic; RELIGION / Christianity / General; Electronic books